DESIGN OF WEB-BASED COURSE INFORMATION SYSTEM FOR THE DALYES COURSE - Melda Agnes Manuhutu (Electro Luceat, 2021)
This research was conducted with the intent and purpose to help provide information about courses in the Sorong City area, especially at the University of Victory Sorong, namely Dalyes Couse. This course previously used introductory media or physical promotional materials such as brochure printing. The researcher intends to create a web-based course application as a modern way to introduce and promote the Dalyes Course. The data collection method used in this research is the waterfall method. The results of this study are the Design of a Web-Based Course Information System for the Dalyes Course which includes the structure of the Dalyes Course and the teacher data in it. Researchers believe that this application can help managers in the promotion process and the learning process. The system is made with the programming language used is PHP and software for designing interfaces using Sublime Text Editor/AdobeDreamweaver CS6. Database creation using MySQL with XAMPP application. The result of this research is a Dalyes Course website with admin functions to add teacher data, manage data edits, schedule inputs and confirm payments. The teacher's function is to upload material, enter value data and absent data. Student functions to download certificates, view grades and course schedules.